Migracje a przemiany miast - Smolarkiewicz, Elżbieta (Człowiek i Społeczeństwo, 2014)
Migrations throughout history constitute one of the most important mechanisms affecting urban development. The conditions of the specificity of the Polish post-war migration determined the linking of the processes of industrialization and urbanization differently than in Western Europe. Thanks to the impressive efforts that ultimately limited the influx of people there has been a slowing down of urban sprawl. The contemporary nature of migration in urban space designates changes in both the economic structure and metropolisation processes. The reversal of the traditional direction of migration generates an increased scale of commuting and disseminates the category of shuttle migrants. The process of metropolisation too enforces change in the migrant profile. There is a strong demand from migrants for the requirement to have a specific socio-cultural capital. The metropolisation differentiates the migration stream, determining the specificity of the city.